PCOS diagnosis in adolescents: the timeline of a controversy in a systematic review - Vassalou, Helen; Sotiraki, Marianthi; Michala, Lina (Journal of Pediatric Endocrinology & Metabolism, 2019)
Study objective Polycystic ovary syndrome (PCOS) in adolescence, a disorder of exclusion, has proved to be a timeless diagnostic challenge for the clinician. Since 1990, several attempts to provide clear diagnostic criteria have been published, most of the time leading to inconsistencies. We attempted to elucidate the controversies and convergences of this subject by conducting a systematic review of the literature concerning official guidelines or proposed criteria for the diagnosis of PCOS in adolescent girls. Design Based on a term search sequence via electronic databases such as Pubmed, Cochrane, Embase, Scopus and a hands-on review of references and learned societies, all available data were classified and analyzed. Single case reports, original studies with adult population or articles with incomplete diagnostic guidelines were excluded. Results Twelve reports dated from 2006 to 2018 fulfilled the inclusion criteria. Seven of them were endorsed or published by learned societies. All suggested a stricter diagnosis than in adulthood. Polycystic ovarian morphology was used as a necessary criterion only in three guidelines, and there was a tendency for a more objective diagnosis of hyperandrogenism, defined either by clinical features or by biochemical hyperandrogenemia, although in one case both were required. Conclusion Irregular menstrual cycles, allowing for an interval of at least 2 years postmenarche, and hyperandrogenism, usually reinforced by biochemical confirmation, are the main accepted features for PCOS diagnosis in adolescence. Discrepancies among endocrine and reproductive medicine societies still remain, although recent intensified attempts at reaching a consensus should allow for more universally accepted diagnostic criteria.